Fundamental Features of 16–18 Years Old Road Cyclists’ Training - Ališauskienė, Rasa; Milašius, Kazys (Pedagogika, 2015)
Lithuanian young cyclists are the winners of various international road cycling events, however, methodic of their preparation, change of their body development, as well as of body and functional capacity indices during yearly training cycle have been of little investigation yet. To have as many as possible objective criteria, helping to ensure a more fluent optimization of road cyclists’ training process and observation of change in their preparedness, it is relevant to carry out investigation on basic features of preparedness and training sessions, so that later on this data would be of use in improving preparation of young road cyclists. The aim of the work was to carry out analysis on young road cyclists’ preparation, change in their body and functional capacities in yearly training cycle, and to provide the summarized results. The results of the research highlighted good preparation of young Lithuanian cyclists in organizational aspect. Training load in yearly cycle reached 1 213 hours, work on road compiled 1006 hours, work on special cycle ergo meter – 118 hours, and 156 hours were allocated for general preparation. In one year, young athletes participated in 437 training sessions, and during them they overcame 22 115 km by bicycle. Muscle power indices of the investigated when performing short duration work did not experience change during the period of investigation. This typical for road cyclists feature was evidenced, confirming the fact that such physical ability is not characteristic to road cyclists. Young cyclists’ indices of special working capacity and indices of blood respiratory system functional capacity used to increase significantly in yearly training cycle. The cyclists, who participated in our research, were successful at Lithuanian and international competitions. The athletes’ demonstrated results testimony the appropriately balanced program of their training, and the progress of the athletes’ body and functional power during yearly training cycle. This allows presuming that these athletes have favorable perspectives to perfect their mastership in future.